Relationship between social support and loneliness among older adults: A cross-sectional study - Yuliana, Yuliana (Science Center Group, 2025)
Background: Loneliness is a prevalent psychosocial problem among older adults and is associated with adverse mental health and quality of life outcomes. Social support has been identified as a potential protective factor that may reduce loneliness in later life; however, empirical evidence among community-dwelling older adults remains limited, particularly in non-institutional settings.Objective: This study aimed to examine the relationship between social support and loneliness among community-dwelling older adults.Methods: This study employed a cross-sectional design involving older adults aged 60 years and above living in the community. Participants were recruited using a non-probability sampling approach based on predefined inclusion criteria. Data were collected through face-to-face interviews using standardized questionnaires to assess perceived social support and loneliness. Descriptive statistics were used to summarize participant characteristics and key variables. Bivariate analysis was conducted to examine the relationship between social support and loneliness.Results: The findings showed that loneliness was prevalent among community-dwelling older adults, with varying levels across the study population. Perceived social support differed according to living arrangements and social participation. Higher levels of perceived social support were significantly associated with lower levels of loneliness. Emotional support demonstrated a stronger association with reduced loneliness compared to other forms of support. The relationship between social support and loneliness remained consistent across selected sociodemographic characteristics.Conclusion: Social support has a significant inverse relationship with loneliness among community-dwelling older adults. Older adults with stronger perceived social support experience lower levels of loneliness.